Optical Responses in Asymmetric Inverse Parabolic Quantum Wells : Efects of Laser Fields and Hydrostatic Pressure (2014)
ABSTRACT: We report the theoretical calculation of the electronic states in a AlxGa1−xAs-based quantum well with inverse parabolic confinement under the combined efects of the intense laser field and hydrostatic pressure. Calculations are in the effective mass and parabolic band approximations and using a variational procedure and the so-called Floquet method in order to obtain the energies and wave functions for the conduction band states. We use the obtained information to investigate the intersubband-related nonlinear optical absorption and optical recti cation coe cients.